Hemodynamic impairments within individual watershed areas in asymptomatic carotid artery stenosis by multimodal MRI. Issue 2 (February 2021) - Kaczmarz, Stephan; Göttler, Jens; Petr, Jan; Hansen, Mikkel Bo; Mouridsen, Kim; Zimmer, Claus; Hyder, Fahmeed; Preibisch, Christine
Improved understanding of complex hemodynamic impairments in asymptomatic internal carotid artery stenosis (ICAS) is crucial to better assess stroke risks. Multimodal MRI is ideal for measuring brain hemodynamics and has the potential to improve diagnostics and treatment selections. We applied MRI-based perfusion and oxygenation-sensitive imaging in ICAS with the hypothesis that the sensitivity to hemodynamic impairments will improve within individual watershed areas (iWSA). We studied cerebral blood flow (CBF), cerebrovascular reactivity (CVR), relative cerebral blood volume (rCBV), relative oxygen extraction fraction (rOEF), oxygen extraction capacity (OEC) and capillary transit-time heterogeneity (CTH) in 29 patients with asymptomatic, unilateral ICAS (age 70.3 ± 7.0 y) and 30 age-matched healthy controls. In ICAS, we found significant impairments of CBF, CVR, rCBV, OEC, and CTH (strongest lateralization ΔCVR = –24%), but not of rOEF. Although the spatial overlap of compromised hemodynamic parameters within each patient varied in a complex manner, most pronounced changes of CBF, CVR and rCBV were detected within iWSAs (strongest effect ΔCVR = +117%). At the same time, CTH impairments were iWSA independent, indicating widespread dysfunction of capillary-level oxygen diffusivity. In summary, complementary MRI-based perfusion and oxygenation parameters offer deeper perspectives on complex microvascular impairments in individual patients. Furthermore, knowledge about iWSAs improves the sensitivity to hemodynamic impairments.